Cardiac Modeling: Identification of Subject Specific Left-Ventricular Isovolumic Pressure Curves. Issue 20 (2015) - Gesenhues, Jonas; Hein, Marc; Albin, Thivaharan; Rossaint, Rolf; Abel, Dirk
Abstract: In this paper we present a mathematical model for isovolumic left-ventricular pressure curves intended for applications in computer simulation models of the cardiovascular system. We chose a quadratic spline to individually account for the specific phases of isovolumic beats. Besides, we describe a method to identify subject specific isovolumic pressure curves based on measured physiological (non-isovolumic) pressure curves. Therefore, we used experimental data obtained from a trial on an anesthetized pig. Specifically, we investigated the effect of a preload reduction for a given contractile state on the isovolumic pressure curves. Towards validation of the proposed model we compared the predicted isovolumic pressure curve to data of real experimentally obtained isovolumic beats. Besides, a comparison to alternative isovolumic pressure curve identification approaches for a different application (estimating contractility by single-beat evaluation) is drawn.